Beyond Botany: In appreciation of the life and contributions of Dini Eisikowitch (1936 – 2022) - Amots Dafni; Peter G Kevan (Journal of Pollination Ecology, 2022)
Professor Dan Eisikowitch (Dini), one of the greatest researchers in 10 pollination and botany, has passed away (1936-2022). Dini died on 19 July, 2022 at 11 the age of 86. An obituary.